Estudios en las Apocynaceae neotropicales IX: Mandevilla antioquiana, sp. nov. y lectotipificación de Echites comosa - J. Francisco Morales (Anales del Jardín Botánico de Madrid)
Mandevilla antioquiana, a new species from the Antioquia Department, Colombia, is described and illustrated, and its taxonomic relationships are discussed. A lectotype is designated for Echites comosa Kuntze.